Inhibiting repulsive guidance molecule-a suppresses secondary progression in mouse models of multiple sclerosis. Issue 11 (November 2018) - Tanabe, Shogo; Fujita, Yuki; Ikuma, Kaori; Yamashita, Toshihide
Abstract Multiple sclerosis (MS) is an autoimmune disease of the central nervous system that is characterized by motor deficits, fatigue, pain, cognitive impairment, and sensory and visual dysfunction. Secondary progressive multiple sclerosis (SPMS) is a progressive form of MS that develops from relapsing-remitting MS. Repulsive guidance molecule-a (RGMa) has diverse functions, including axon growth inhibition and immune regulation. Here, we show inhibiting RGMa had therapeutic effects in mouse models of SPMS. We induced experimental autoimmune encephalomyelitis in nonobese diabetic mice (NOD-EAE mice) and treated them with humanized anti-RGMa monoclonal antibody. This treatment significantly suppressed secondary progression of disease and inflammation, demyelination and axonal degeneration. In addition, treatment with anti-RGMa antibody promoted the growth of corticospinal tracts and motor recovery in targeted EAE mice with inflammatory lesions in the spinal cord. Collectively, these results show that a humanized anti-RGMa antibody has therapeutic effects in mouse models of SPMS.